3D printed polymer dielectric substrates with enhanced permittivity by nanoclay inclusion. Issue 2 (3rd April 2017) - Francis, Vishal; Jain, Prashant K.
ABSTRACT: 3D printing technique has become an attractive tool to fabricate complex functional object and is widely utilised in various sectors. Electronics and communications is one such sector that has adopted 3D printing for fabrication of devices requiring dielectric substrate materials. However, the commercially available printable materials have limited range of permittivity. Polymer clay nanocomposites (PCNs) have the potential to alter the dielectric properties of the polymers. Nanoclay based composites were developed by modification of acrylonitrile butadiene styrene filament for 3D printing. The nanocomposites were characterised for their dielectric properties. The developed PCN showed enhancement in permittivity values as compared to the pristine polymer. The ionic nature of nanoclay and the fused network of nanoclay/polymer developed during 3D printing promotes enhancement in dielectric properties. Moreover, hybrid patterned specimens were 3D printed utilising the polymer and nanocomposite filaments to investigate the variation in dielectric properties occurred because of different patterns.